Metal-doped carbon quantum dot and preparation method thereof
By using Schiff alkali metal complex for coordination reaction, the metal is stably doped to the center of the carbon quantum dot, the problems of low doping rate and poor product performance in the prior art are solved, and high doping rate and Preparation of metal-doped carbon quantum dots with excellent performance.
Patent Information
- Application Number
- CN202411459305.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The prior art faces the adverse effects of low doping rates and oxidation or reduction properties of metal ions on product performance during the preparation of metal-doped carbon quantum dots.
Using Schiff alkali metal complex as a precursor, the metal is stably doped to the center of the carbon quantum dot by coordination reaction, improving the doping rate and optimizing product performance.
High doping rates and better product performance are achieved. The prepared iron and manganese doped carbon quantum dots have peroxidase mimicry activity and superoxide dismutase activity, and have good antioxidant ability.
Smart Images

Figure CN119391409A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon quantum dots, and in particular relates to metal-doped carbon quantum dots and a preparation method thereof. Background Art
[0002] Carbon quantum dots (CDs) can generally be defined as spherical carbon nanoparticles with excellent fluorescence properties and a size less than 10 nm. With the advantages of good dispersibility, biocompatibility, low toxicity, easy functionalization, abundant raw materials and low cost, they have been widely used in optoelectronic devices, photocatalysis, bioimaging, biomedicine, chemical sensing and biotherapy. Doping is an effective method to regulate the physicochemical properties of carbon dots (CDs) and has received increasing attention in recent years. After CDs are doped with heteroatoms, their electronic structure, nanostructure and chemical composition will change due to the overlap of atomic orbitals of heteroatoms and carbon atoms, as well as the push-pull electron effect of heteroatoms. Compared with non-metallic atoms, metal ions have more electrons and unoccupied orbitals, as well as larger atomic radii. Doping CDs with metal ions can cause significant changes in optical, electronic and magnetic properties by changing the electron density distribution and energy gap of CDs.
[0003] At present, there are some difficult problems in the preparation process of metal-doped carbon quantum dots: 1) The metal doping rate is low. This is because metal ions will generate nano-metal oxides during the solvothermal process, which will bring many negative effects; the generation of nano-metal oxides may interfere with the synthesis reaction of carbon quantum dots, resulting in the reaction being hindered, thereby reducing the efficiency and yield of the reaction; the generation of nano-metal oxides may also affect the purity of the product, further reducing the doping rate; 2) The oxidation or reduction properties of metal ions have an adverse effect on the performance of the product; metal ions with oxidizing properties may undergo oxidation reactions with other substances in the reaction system, thereby changing the reaction path and the distribution of the products, causing the properties and structure of the generated carbon quantum dots to change, affecting their performance and application; metal ions with reducing properties may participate in the reduction reaction, consume the oxidant or reductant in the reaction system, thereby affecting the reaction; in addition, metal ions with reducing properties may also cause the generated carbon quantum dots to have too much negative charge on the surface, affecting their stability and solubility. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a metal-doped carbon quantum dot and a preparation method thereof in view of the deficiencies in the prior art. By using a Schiff base metal complex as a precursor, the metal can be stably doped into the center of the carbon quantum dot to obtain a higher doping rate and better product performance.
[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing metal-doped carbon quantum dots, comprising the following steps:
[0006] 1) dissolving 2,5-dihydroxybenzaldehyde in ethanol to obtain a first solution, dissolving o-phenylenediamine in ethanol to obtain a second solution, and dropping the second solution into the first solution to react. After the reaction is completed, filtering and retaining solids, washing, and drying to obtain a Schiff base compound;
[0007] 2) adding the Schiff base compound to ethanol and heating it to completely dissolve it to obtain a third solution, dissolving the metal salt in ethanol to obtain a fourth solution, and dropping the fourth solution into the third solution to carry out a coordination reaction. After the reaction is completed, filtering and retaining the solid, washing, and drying to obtain a metal coordinated Schiff base compound;
[0008] 3) dissolving the metal-coordinated Schiff base compound in a solvent, then adding the carboxyl compound and performing ultrasound until it is completely dissolved, heating the mixture to react, centrifuging and collecting the supernatant after the reaction is completed, dialyzing the supernatant, and freeze-drying the supernatant to obtain metal-doped carbon quantum dots.
[0009] In the above scheme, in the first solution, the volume ratio of the amount of 2,5-dihydroxybenzaldehyde to ethanol is 1 mmol: (2-20) mL.
[0010] In the above scheme, in the second solution, the volume ratio of the amount of o-phenylenediamine to ethanol is 1 mmol: (2 to 25) mL.
[0011] In the above scheme, the molar ratio of o-phenylenediamine to 2,5-dihydroxybenzaldehyde is 1:(2-3).
[0012] In the above scheme, the reaction temperature in step 1) is 60-80° C. and the reaction time is 3-8 h.
[0013] In the above scheme, in step 1), the obtained solid is washed with ethanol and dried at 40-70°C.
[0014] In the above scheme, the structural formula of the Schiff base compound is:
[0015]
[0016] In the above scheme, in the third solution, the volume ratio of the amount of the Schiff base compound to ethanol is 1 mmol: (1-40) mL.
[0017] In the above scheme, in the fourth solution, the volume ratio of the amount of metal salt to ethanol is 1 mmol: (1 to 30) mL.
[0018] In the above scheme, the molar ratio of the Schiff base compound to the metal salt is 1:(1-2).
[0019] In the above scheme, the metal in the metal salt is one of manganese, iron, cobalt, nickel, copper, zinc, ruthenium and platinum.
[0020] In the above scheme, in step 2), the reaction temperature of the coordination reaction is 60 to 80° C., and the reaction time is 4 to 10 hours.
[0021] In the above scheme, in step 2), the obtained solid is washed with ethanol and dried at 40-70°C.
[0022] In the above scheme, the structural formula of the metal-coordinated Schiff base compound is:
[0023]
[0024] In the formula, M is selected from one of Mn, Fe, Co, Ni, Cu, Zn, Ru and Pt.
[0025] In the above scheme, the solvent is one of water, ethanol and N-N-dimethylformamide.
[0026] In the above scheme, the mass ratio of the metal-coordinated Schiff base compound to the volume of the solvent is 1 mg: (1-5) mL.
[0027] In the above scheme, the carboxyl-containing compound is one of citric acid, tartaric acid, malic acid, pyromellitic acid, and amino acid.
[0028] In the above scheme, the mass ratio of the metal coordinated Schiff base compound to the carboxyl-containing compound is 1:(5-20).
[0029] In the above scheme, the ultrasonic time is 5 to 30 minutes.
[0030] In the above scheme, in step 3), the reaction temperature of the temperature-raising reaction is 120-200° C., and the reaction time is 4-8 hours.
[0031] In the above scheme, the molecular weight cutoff of the dialysis is 500-1200Da, and the dialysis time is 36-72h.
[0032] In the above scheme, the freeze-drying temperature is -40 to -80°C and the time is 6 to 48 hours.
[0033] The present invention also provides a metal-doped carbon quantum dot, which is prepared by the above method.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1) The present invention uses a Schiff base metal complex as a precursor. The nitrogen atoms in the Schiff base can form coordination bonds with metal ions. The formation of such chemical bonds increases the stability of the complex, enabling it to be doped with metals with a stable structure and ensuring that the metal is doped into the center of the carbon quantum dots rather than the surface, thereby obtaining a higher doping rate and better product performance.
[0036] 2) The iron-doped carbon quantum dots prepared by the present invention have peroxidase mimicking activity and can catalyze hydrogen peroxide to produce reactive oxygen. The manganese-doped carbon quantum dots prepared by the present invention have superoxide dismutase activity and can remove superoxide anions and have good antioxidant capacity.
[0037] 3) The preparation method of the metal-doped carbon quantum dots of the present invention has easy-to-obtain reaction raw materials, a simple synthesis method, and is easy for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a fluorescence image of the iron-doped carbon quantum dots prepared in Example 1 after being dissolved in N,N-dimethylformamide under 365nm laser irradiation.
[0039] Figure 2 This is a transmission electron microscopy image of the iron-doped carbon quantum dots prepared in Example 1.
[0040] Figure 3 This is the ultraviolet absorption spectrum of the iron-doped carbon quantum dots prepared in Example 1 in deionized water.
[0041] Figure 4 This is the fluorescence emission spectrum of the iron-doped carbon quantum dots prepared in Example 1 when excited at different excitation wavelengths in N,N-dimethylformamide.
[0042] Figure 5 This is the infrared spectrum of the iron-doped carbon quantum dots prepared in Example 1.
[0043] Figure 6 The iron-doped carbon quantum dots prepared in Example 1 are used for TMB+H 2 O 2 UV absorption spectrum of the reaction.
[0044] Figure 7 The iron-doped carbon quantum dots prepared in Example 1 are used for TMB+H 2 O 2 The solution changes color during the reaction.
[0045] Figure 8 This is the effect of the iron-doped carbon quantum dots prepared in Example 1 on the catalytic activity of the simulated enzyme under different coexisting substances.
[0046] Fig. 9This is the effect of the iron-doped carbon quantum dots prepared in Example 1 on the catalytic activity of the simulated enzyme at different storage times.
[0047] Fig.10 XPS graphs of iron-doped carbon quantum dots prepared in Example 1 and Comparative Example 1.
[0048] Fig.11 The fluorescence emission spectra of the iron-doped carbon quantum dots prepared in Comparative Example 1 and Comparative Example 2 generated by being excited at different excitation wavelengths in N,N-dimethylformamide.
[0049] Fig.12 The iron-doped carbon quantum dots prepared in Comparative Examples 1 and 2 react with TMB+H 2 O 2 UV absorption spectrum of the reaction.
[0050] Fig.13 The iron-doped carbon quantum dots prepared in Example 1, Comparative Example 1 and Comparative Example 2 were prepared with H 2 O 2 Michaelis-Menten curve and Lineweaver-Burk plot for substrate analysis.
[0051] Fig.14 This is a fluorescence image of the manganese-doped carbon quantum dots prepared in Example 2 after being dissolved in N,N-dimethylformamide under 365nm laser irradiation.
[0052] Fig.15 The maximum excitation wavelength and maximum emission wavelength of the manganese-doped carbon quantum dots prepared in Example 2 in N,N-dimethylformamide.
[0053] Fig.16 The scavenging effect of the manganese-doped carbon quantum dots prepared in Example 2 on superoxide anions at different concentrations.
[0054] Fig.17 The scavenging effect of manganese-doped carbon quantum dots prepared in Example 2 on DPPH at different concentrations.
[0055] Fig.18 The scavenging effect of the manganese-doped carbon quantum dots prepared in Example 2 on ABTS at different concentrations. DETAILED DESCRIPTION
[0056] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0057] Example 1
[0058] This embodiment prepares an iron-doped carbon quantum dot, comprising the following steps:
[0059] 1) dissolving 1.21 mmol 2,5-dihydroxybenzaldehyde in 3 mL ethanol to obtain a first solution, dissolving 0.55 mmol o-phenylenediamine in 2 mL ethanol to obtain a second solution, dropping the second solution into the first solution, heating to 65° C. and reflux for reaction for 5 h, filtering and retaining the solid after the reaction, washing with ethanol and drying at 50° C. to obtain a Schiff base compound;
[0060]
[0061] 2) Add 0.19 mmol of Schiff base compound to 5 mL of ethanol and heat to 65°C to completely dissolve it to obtain a third solution. Add 0.19 mmol of FeCl 3 6H 2 O is dissolved in 2 mL of ethanol to obtain a fourth solution, the fourth solution is added dropwise to the third solution, and the mixture is refluxed at 65° C. for 5 h. After the reaction is completed, the solid is filtered and retained, washed with ethanol, and dried at 50° C. to obtain an iron-coordinated Schiff base compound;
[0062]
[0063] 3) 50 mg of the iron-coordinated Schiff base compound was dissolved in 50 mL of N,N-dimethylformamide, and then 500 mg of citric acid was added and ultrasonicated for 20 min until completely dissolved, and then transferred to a reactor and placed in a programmable temperature-controlled oven. The reaction temperature was set to 160°C for 8 h. After the reaction was completed, the supernatant was centrifuged and retained. The supernatant was dialyzed for 36 h using a dialysis bag with a molecular weight cutoff of 1000 Da, and then freeze-dried at -50°C under vacuum conditions for 24 h to obtain iron-doped carbon quantum dots, which were recorded as salen-Fe-CDs.
[0064] Figure 1 The fluorescence image of the iron-doped carbon quantum dots prepared in this example after being dissolved in N,N-dimethylformamide under 365nm laser irradiation clearly shows that it is green fluorescence.
[0065] Figure 2 This is a transmission electron microscope image of the iron-doped carbon quantum dots prepared in this example. It can be seen from the observation that the prepared carbon quantum dots are spherical and have good dispersion. Analysis shows that the average particle size of the prepared carbon quantum dots is about 2.31 nm.
[0066] Figure 3 The UV absorption spectrum of the iron-doped carbon quantum dots prepared in this example in deionized water shows an absorption peak at 270 nm, which can be attributed to the π→π * Transition.
[0067] Figure 4The iron-doped carbon quantum dots prepared in this example generate fluorescence emission spectra when excited at different excitation wavelengths in N,N-dimethylformamide, and the maximum excitation wavelength is 360 nm.
[0068] Figure 5 This is the infrared spectrum of the iron-doped carbon quantum dots prepared in Example 1, 3426 cm -1 The peak at 2928cm is attributed to the C-OH / OH group; -1 、1624cm -1 , and 1455cm -1 The peak at 1125 cm is attributed to CH / C=O and CN stretching vibrations; -1 and 652cm -1 The peak signals at are attributed to Fe-N and Fe-O stretching vibrations, respectively; these results prove that there are hydroxyl groups and functional groups such as nitrogen-containing compounds on the surface of iron-doped carbon quantum dots, and that iron elements have been successfully doped into carbon quantum dots and formed chemical bonds with nitrogen and oxygen atoms.
[0069] The simulated enzyme activity of the iron-doped carbon quantum dots prepared in this example was tested by adding iron-doped carbon quantum dots (0.3 mg / mL), H 2 O 2 (0.33mmol / L) and 3,3',5,5'-tetramethylbenzidine TMB (0.16mmol / L) were reacted at room temperature for 3min. 2 O 2 of the control group; Figure 7 The results show that the color of TMB+salen-Fe-CDs system did not change, while the color of TMB+salen-Fe-CDs+H 2 O 2 The color of the system changes to blue visible to the naked eye, and Figure 6 TMB+salen-Fe-CDs+H 2 O 2 The system showed an absorption signal at 652 nm, indicating that the iron-doped carbon quantum dots had peroxidase mimicking activity, which could catalyze hydrogen peroxide to produce reactive oxygen species and oxidize the colorless TMB into a stable blue product, ox-TMB.
[0070] The enzyme stability of the iron-doped carbon quantum dots prepared in this example was tested. First, the effect of coexisting substances on its catalytic activity was tested. 2 O 2 0.1mL (10mmol / L) of coexisting substances were added to the system. Figure 8It can be seen that the catalytic performance of iron-doped carbon quantum dots is almost unaffected by these coexisting substances. Secondly, the effect of storage time on its catalytic activity was tested. The prepared carbon quantum dots were stored in a dry state at room temperature for 15 days. Fig. 9 It can be seen that the iron-doped carbon quantum dots still maintain a high peroxidase mimetic activity after long-term storage.
[0071] Comparative Example 1
[0072] This comparative example prepares an iron-doped carbon quantum dot (FeCl 3 -CDs), including the following steps:
[0073] 50 mg FeCl 3 6H 2 O was dissolved in 50 mL N,N-dimethylformamide, and then 500 mg citric acid was added and ultrasonicated for 20 min until completely dissolved, and then transferred to a reactor and placed in a programmable temperature-controlled oven. The reaction temperature was set to 160 ° C for 8 h. After the reaction was completed, the supernatant was centrifuged and separated. The supernatant was dialyzed for 36 h using a dialysis bag with a molecular weight cutoff of 1000 Da, and then freeze-dried at -50 ° C under vacuum conditions for 24 h to obtain iron-doped carbon quantum dots, which were recorded as FeCl 3 -CDs.
[0074] Comparative Example 2
[0075] This comparative example prepares an iron-doped carbon quantum dots (EDTA-Fe-CDs), comprising the following steps:
[0076] 50 mg of sodium iron ethylenediaminetetraacetate was dissolved in 50 mL of N,N-dimethylformamide, and then 500 mg of citric acid was added and ultrasonicated for 20 minutes until completely dissolved. Then, the mixture was transferred to a reactor and placed in a programmable temperature-controlled oven. The reaction temperature was set to 160°C and the reaction was carried out for 8 hours. After the reaction was completed, the supernatant was centrifuged and retained. The supernatant was dialyzed for 36 hours using a dialysis bag with a molecular weight cutoff of 1000 Da, and then freeze-dried at -50°C under vacuum conditions for 24 hours to obtain iron-doped carbon quantum dots, which were recorded as EDTA-Fe-CDs.
[0077] Fig.10 The XPS graphs of iron-doped carbon quantum dots prepared in Example 1 and Comparative Example 1 are shown in Table 1. 3 6H 2 O, the amount of iron doping in the product is small and difficult to detect. 3 6H 2 O dosage was adjusted to 250 mg and a new set of FeCl 3-CDs were tested. From the results of element content analysis, it can be seen that the iron content of comparative example 1 is 0.82%, and the iron content of example 1 is 0.65%. However, the raw material FeCl used to prepare carbon dots in comparative example 1 is 3 6H 2 The amount of O used is 5 times the amount of the raw material iron-coordinated Schiff base compound used to prepare carbon dots in Example 1, so the iron doping rate of Example 1 is actually relatively high.
[0078] Fig.11 The fluorescence emission spectra of the iron-doped carbon quantum dots prepared in Comparative Examples 1 and 2 are excited in N,N-dimethylformamide at different excitation wavelengths. It can be seen from the figure that the maximum emission wavelength of the iron-doped carbon quantum dots prepared in Comparative Examples 1 and 2 is 440nm, while Figure 4 It is shown that the maximum emission wavelength of the iron-doped carbon quantum dots prepared in Example 1 is 520 nm. From the perspective of fluorescence performance, when the Schiff base iron complex is used as a precursor to prepare carbon dots, a larger effective conjugated structure may be formed during the carbonization process. This conjugated structure helps to promote the delocalization and transition of electrons, thereby affecting the luminescent properties of the carbon dots, including the red shift of the emission wavelength.
[0079] The simulated enzyme activity of the iron-doped carbon quantum dots prepared in Comparative Example 1 and Comparative Example 2 was tested. Iron-doped carbon quantum dots (0.3 mg / mL), H 2 O 2 (0.1mmol / L) and TMB (0.25mmol / L), react at room temperature for 3min; Fig.12 It can be seen that under the same conditions, the iron-doped carbon quantum dots prepared in Example 1 have the highest absorption value at 652 nm and have better peroxidase-like activity.
[0080] To further compare the catalytic ability, H 2 O 2 The Michaelis constants (K m ), where K m The value represents the affinity between the substrate and the carbon dot mimetic enzyme, K m The smaller it is, the stronger the affinity is. Fig.13 It shows that the K of comparative example 1 m is 0.11, and K of comparative example 2 m is 0.085, and K of Example 1 m According to the value of Km, it can be seen that the iron-doped carbon quantum dots prepared in Example 1 have a strong affinity for H 2 O 2 The affinity is the strongest and has better peroxidase-like activity than the control example.
[0081] Example 2
[0082] This embodiment prepares a manganese-doped carbon quantum dot, comprising the following steps:
[0083] 1) dissolving 7 mmol 2,5-dihydroxybenzaldehyde in 20 mL ethanol to obtain a first solution, dissolving 3.5 mmol o-phenylenediamine in 10 mL ethanol to obtain a second solution, adding the second solution dropwise to the first solution, and heating to 70° C. to reflux for reaction for 4.5 h. After the reaction is completed, filtering and retaining the solid, washing with ethanol and drying at 60° C. to obtain a Schiff base compound;
[0084] 2) 0.078 mmol of Schiff base compound was added to 3 mL of ethanol and heated to 65°C to completely dissolve it to obtain a third solution, and 0.078 mmol of Mn(OAc) 2 ·4H 2 O is dissolved in 2 mL of ethanol to obtain a fourth solution, the fourth solution is added dropwise to the third solution, and the mixture is refluxed at 70° C. for 5 h. After the reaction is completed, the solid is filtered and retained, and the solid is washed with ethanol and dried at 60° C. to obtain a manganese-coordinated Schiff base compound;
[0085] 3) 50 mg of the manganese-coordinated Schiff base compound was dissolved in 50 mL of N,N-dimethylformamide, and then 500 mg of citric acid was added and ultrasonicated for 20 min until completely dissolved, and then transferred to a reactor and placed in a programmable temperature-controlled oven. The reaction temperature was set to 180 ° C and the reaction was carried out for 8 hours. After the reaction was completed, the supernatant was centrifuged and retained. The supernatant was dialyzed for 36 hours using a dialysis bag with a molecular weight cutoff of 1000 Da, and then freeze-dried at -50 ° C under vacuum conditions for 28 hours to obtain manganese-doped carbon quantum dots.
[0086] Fig.14 The fluorescence image of the manganese-doped carbon quantum dots prepared in this example after being dissolved in N,N-dimethylformamide under 365nm laser irradiation clearly shows that it is yellow-green fluorescence.
[0087] The optical properties of the manganese-doped carbon quantum dots prepared in this example were tested, and their absorption spectrum in DMF solution was measured. Fig.15 As shown, the maximum excitation wavelength is 350 nm and the maximum emission wavelength is 520 nm.
[0088] The simulated superoxide dismutase activity of the manganese-doped carbon quantum dots prepared in this example was studied, and nitro blue tetrazolium chloride (NBT) was used as a probe to determine its scavenging effect on superoxide anions. The test principle is that NBT can react with superoxide anions to generate formazan in the solution and appear blue, with a peak at 560nm. When a superoxide anion scavenger is present, the peak will decrease. Fig.16As shown, with the increase of the concentration of manganese-doped carbon quantum dots, the absorbance value of the solution at 560nm dropped sharply, and the superoxide anion scavenging rate reached 80% at a concentration of 40 μg / mL, indicating that the manganese-doped carbon quantum dots prepared in this example have excellent superoxide anion scavenging rate.
[0089] The antioxidant activity of the manganese-doped carbon quantum dots prepared in this example was investigated, and their activity in scavenging reactive oxygen free radicals was detected. DPPH (2,2-biphenyl-1-picrylhydrazyl) was selected as a model free radical. DPPH exhibits a characteristic absorption peak at 515nm. When DPPH comes into contact with a free radical scavenger, the peak value decreases due to the formation of a DPPH complex. The elimination of DPPH represents the antioxidant capacity. Fig.17 As shown, as the concentration of manganese-doped carbon quantum dots increased from 0 to 150 μg / mL, the peak intensity at 517 nm showed a continuous downward trend, and the DPPH scavenging rate also increased to 89.84%, indicating that the manganese-doped carbon quantum dots prepared in this example have higher DPPH scavenging activity and stronger antioxidant activity.
[0090] In addition, ABTS (2,2-azino-bis(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt) was selected as a model group. + Free radicals need to obtain electrons from antioxidant molecules to form stable neutral molecules, and the free radical scavenging activity of manganese-doped carbon quantum dots was evaluated by the decrease in their absorbance at 734 nm. Fig.18 As shown in Figure 2, with the increase of manganese-doped carbon quantum dots concentration (5-150 μg / mL), ABTS + The scavenging rate also increased from 6.42% to 91.27%. The results show that the manganese-doped carbon quantum dots prepared in this example have excellent antioxidant capacity and can effectively scavenge ABTS free radicals.
[0091] Example 3
[0092] This embodiment prepares a platinum-doped carbon quantum dot, comprising the following steps:
[0093] 1) dissolving 2 mmol 2,5-dihydroxybenzaldehyde in 10 mL ethanol to obtain a first solution, dissolving 1 mmol o-phenylenediamine in 5 mL ethanol to obtain a second solution, adding the second solution dropwise to the first solution, and heating to 68° C. to reflux for 6 h. After the reaction is completed, filtering and retaining the solid, washing with ethanol and drying at 46° C. to obtain a Schiff base compound;
[0094] 2) Add 1 mmol of Schiff base compound to 5 mL of ethanol and heat to 65°C to completely dissolve it to obtain a third solution. Add 1 mmol of PtCl 4The fourth solution was dissolved in 3 mL of ethanol to obtain a fourth solution, and the fourth solution was added dropwise to the third solution, and the mixture was refluxed at 68° C. for 6 h. After the reaction was completed, the solid was filtered and retained, and the solid was washed with ethanol and dried at 46° C. to obtain a platinum-coordinated Schiff base compound;
[0095] 3) 25 mg of platinum-coordinated Schiff base compound was dissolved in 25 mL of ethanol, and then 400 mg of tartaric acid was added and ultrasonicated for 25 min until completely dissolved, and then transferred to a reactor and placed in a programmable temperature-controlled oven. The reaction temperature was set to 185 ° C and the reaction was carried out for 4 hours. After the reaction was completed, the supernatant was centrifuged and retained. The clear liquid was dialyzed for 48 hours using a dialysis bag with a molecular weight cutoff of 1000 Da, and then freeze-dried at -60 ° C under vacuum conditions for 30 hours to obtain platinum-doped carbon quantum dots.
[0096] Example 4
[0097] This embodiment prepares a copper-doped carbon quantum dot, comprising the following steps:
[0098] 1) dissolving 2.5 mmol 2,5-dihydroxybenzaldehyde in 15 mL ethanol to obtain a first solution, dissolving 1 mmol o-phenylenediamine in 6 mL ethanol to obtain a second solution, dropping the second solution into the first solution, and heating to 76° C. to reflux for 4 h. After the reaction is completed, filtering and retaining the solid, washing with ethanol and drying at 48° C. to obtain a Schiff base compound;
[0099] 2) 1.5 mmol of Schiff base compound was added to 8 mL of ethanol and heated to 70°C to completely dissolve it to obtain a third solution. 1.6 mmol of CuCl 2 The fourth solution was dissolved in 7 mL of ethanol to obtain a fourth solution, and the fourth solution was added dropwise to the third solution, and the mixture was refluxed at 76° C. for 7 h. After the reaction was completed, the solid was filtered and retained, and the solid was washed with ethanol and dried at 48° C. to obtain a copper-coordinated Schiff base compound;
[0100] 3) Dissolve 50 mg of copper-coordinated Schiff base compound in 60 mL of deionized water, then add 700 mg of glycine and sonicate for 25 min until completely dissolved, then transfer to a reactor and place in a programmable temperature-controlled oven. Set the reaction temperature to 170 ° C and react for 5 h. After the reaction is completed, centrifuge and separate the supernatant. After dialyzing the supernatant for 24 h using a dialysis bag with a molecular weight cutoff of 1200 Da, freeze-dry at -45 ° C under vacuum conditions for 30 h to obtain copper-doped carbon quantum dots.
[0101] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A method for preparing metal-doped carbon quantum dots, characterized in that: The following steps are involved: 1) dissolving 2,5-dihydroxybenzaldehyde in ethanol to obtain a first solution, dissolving o-phenylenediamine in ethanol to obtain a second solution, and dropping the second solution into the first solution to react. After the reaction is completed, filtering and retaining solids, washing, and drying to obtain a Schiff base compound; 2) adding the Schiff base compound to ethanol and heating it to completely dissolve it to obtain a third solution, dissolving the metal salt in ethanol to obtain a fourth solution, and dropping the fourth solution into the third solution to carry out a coordination reaction. After the reaction is completed, filtering and retaining the solid, washing, and drying to obtain a metal coordinated Schiff base compound; 3) dissolving the metal-coordinated Schiff base compound in a solvent, then adding the carboxyl compound and performing ultrasound until it is completely dissolved, heating the mixture to react, centrifuging and collecting the supernatant after the reaction is completed, dialyzing the supernatant, and freeze-drying the supernatant to obtain metal-doped carbon quantum dots.
2. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: The molar ratio of o-phenylenediamine to 2,5-dihydroxybenzaldehyde is 1:(2-3); the reaction temperature in step 1) is 60-80° C., and the reaction time is 3-8 hours.
3. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: The molar ratio of the Schiff base compound to the metal salt is 1:(1-2); the reaction temperature of the coordination reaction in step 2) is 60-80°C, and the reaction time is 4-10h; the metal in the metal salt is one of manganese, iron, cobalt, nickel, copper, zinc, ruthenium, and platinum.
4. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: The structural formula of the metal-coordinated Schiff base compound is: In the formula, M is selected from one of Mn, Fe, Co, Ni, Cu, Zn, Ru and Pt.
5. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: The mass ratio of the metal coordinated Schiff base compound to the carboxyl-containing compound is 1:(5-20); the reaction temperature of the temperature-raising reaction in step 3) is 120-200° C., and the reaction time is 4-8 hours.
6. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: The solvent is one of water, ethanol, and NN dimethylformamide; the mass ratio of the metal-coordinated Schiff base compound to the volume of the solvent is 1 mg: (1-5) mL; the carboxyl-containing compound is one of citric acid, tartaric acid, malic acid, pyromellitic acid, and amino acid.
7. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: In the first solution, the volume ratio of the amount of 2,5-dihydroxybenzaldehyde to ethanol is 1 mmol:(2-20) mL; in the second solution, the volume ratio of the amount of o-phenylenediamine to ethanol is 1 mmol:(2-25) mL.
8. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: In the third solution, the volume ratio of the amount of the Schiff base compound to ethanol is 1 mmol:(1-40) mL; in the fourth solution, the volume ratio of the amount of the metal salt to ethanol is 1 mmol:(1-30) mL.
9. The method for preparing metal-doped carbon quantum dots according to claim 1, characterized in that: The molecular weight cut-off of the dialysis is 500 to 1200 Da, and the dialysis time is 36 to 72 hours; the temperature of the freeze-drying is -40 to -80°C, and the time is 6 to 48 hours.
10. Metal-doped carbon quantum dots prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Salophen type bis-Schiff base photochromic material and its preparation method
CN102516980A
Tetradentate schiff base metal complexes, metal porphyrin complexes and preparing method of polycarbonate
CN102558199A
Preparation method of metal doped fluorescent carbon quantum dot
CN109468130A
Polymer xifualkali phthalocyanin bimetal compound, its preparation method and application
CN1948365A
Cited By
Preparation and application of high-entropy alloy micro-electrolysis filler for water treatment
CN121181099A